2014
DOI: 10.1097/opx.0000000000000314
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Central Vision Loss on Perception of Mutual Gaze

Abstract: Purpose To evaluate the effects of central vision loss (CVL) on mutual gaze perception (knowing whether somebody else is looking at you), an important nonverbal visual cue in social interactions. Methods 23 persons with CVL (visual acuity 20/50 to 20/200), 16 with a bilateral central scotoma and 7 without, and 23 age-matched controls completed a gaze perception task, and a brief questionnaire. They adjusted the eyes of a life-size virtual head on a monitor at a 1-m distance until they appeared either to be l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…Thus, even complex visual processes that leave room for compensation were negatively affected by the scotoma. Surprisingly, apart from the increased variability, the central vision loss affected our patients to a remarkably small extent when judging mutual gaze (Sheldon et al, 2014). In the current study, the healthy subjects appeared to compensate for the impairment by tightening their criterion for mutual gaze when confronted with dioptric blur or a diffusing filter, which could point to a process by which patients adapt to their visual impairment and are able to achieve close to normal performance with regard to higher-order visual perception although their acuity is compromised.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Thus, even complex visual processes that leave room for compensation were negatively affected by the scotoma. Surprisingly, apart from the increased variability, the central vision loss affected our patients to a remarkably small extent when judging mutual gaze (Sheldon et al, 2014). In the current study, the healthy subjects appeared to compensate for the impairment by tightening their criterion for mutual gaze when confronted with dioptric blur or a diffusing filter, which could point to a process by which patients adapt to their visual impairment and are able to achieve close to normal performance with regard to higher-order visual perception although their acuity is compromised.…”
Section: Discussionmentioning
confidence: 81%
“…We previously found that patients with central vision loss that included a central scotoma (a blind area in central vision) had significantly more variable gaze direction judgments than age-matched normally-sighted subjects (Sheldon, Quint, Hecht & Bowers, 2014). Our present simulations produced similar results in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, this finding is consistent with the fact that group situations pose the most challenging setting for face perception. That is, to fully engage in a group social interaction, one needs to be able to: rapidly identify all members of the group; pick up immediately on rapid changes of expression or emotion and what events these were in response to; use eye gaze cues to pick up on social signals such as when it might be your turn to speak or when the group's attention has shifted elsewhere [37]; and potentially use facial speech cues to help understand what others are saying (particularly in a noisy environment [38]).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, Ng et al 30 show that there has been a substantial increase in the usage of anti-VEGF agents for both typical AMD and PCV in one center. Sheldon et al 32 investigated this issue in patients with central vision loss and demonstrate that those with central vision loss have remarkably intact mutual gaze. That is the perception that someone is looking at them, which is an important nonverbal social cue.…”
Section: Clinical Management Of Late-stage Amdmentioning
confidence: 99%